Ambient PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) in Changhua County, central Taiwan: Seasonal variation, source apportionment and cancer risk assessment. (November 2016) - Chen, Yu-Cheng; Chiang, Hung-Che; Hsu, Chin-Yu; Yang, Tzu-Ting; Lin, Tzu-Yu; Chen, Mu-Jean; Chen, Nai-Tzu; Wu, Yuh-Shen
Abstract: This study investigates PM2.5 -bound PAHs for rural sites (Dacheng and Fangyuan) positioned close to heavy air-polluting industries in Changhua County, central Taiwan. A total of 113 PM2.5 samples with 22 PAHs collected from 2014 to 2015 were analyzed, and Positive Matrix Factorization (PMF) and diagnostic ratios of PAHs were applied to quantify potential PAH sources. The influences of local and regional sources were also explored using the conditional probability function (CPF) and potential source contribution function (PSCF) with PMF-modeled results, respectively. Annual mean concentrations of total PAHs were 2.91 ± 1.34 and 3.04 ± 1.40 ng/m 3 for Dacheng and Fangyuan, respectively, and their corresponding BaPeq were measured at 0.534 ± 0.255 and 0.563 ± 0.273 ng/m 3 in concentration. Seasonal variations with higher PAHs found for the winter than for the spring and summer were observed for both sites. The lifetime excess cancer risk (ECR) from inhalation exposure to PAHs was recorded as 4.7 × 10 −5 overall. Potential sources of PM2.5 -bound PAHs include unburned petroleum and traffic emissions (42%), steel industry and coal combustion (31%), and petroleum and oil burning (27%), and unburned petroleum and traffic emission could contribute the highest ECR (2.4 × 10 −5 ). The CPF results show that directional apportionment patterns were consistent with the actual locations of local PAH sources. The PSCF results indicate that mainly northeastern regions of China have contributed elevated PM2.5 -bound PAHs from long-range transports. Highlights: Characteristics of PAHs in PM2.5 were first investigated in Changhua County. PAH concentrations were higher in winter than other seasons. The unburned petroleum and traffic emission was predominant for PAH contributions. The ECR from inhalation exposure to PAHs was 47 × 10 −6 . Abstract : Three potential sources of PM2.5 -bound PAHs were obtained, and the ECR of inhalation exposure to PAHs was higher than the USEPA guideline limit.